2016
DOI: 10.3389/fpls.2016.00313
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Comparison of Reference Genes for qPCR Normalization of Celery (Apium graveolens) at Different Development Stages

Abstract: A suitable reference gene is an important prerequisite for guarantying accurate and reliable results in qPCR analysis. Celery is one of the representative vegetable in Apiaceae and is widely cultivated and consumed in the world. However, no reports have been previously published concerning reference genes in celery. In this study, the expression stabilities of nine candidate reference genes in leaf blade and petiole at different development stages were evaluated using three statistics algorithms geNorm, NormFi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 50 publications
6
62
1
Order By: Relevance
“…Primer amplification efficiency indicates the amplicon doubling rate of a specific primer pair during a PCR, which affects the accuracy of RT-qPCR data [4,40]. A good primer combination has an E value close to 100% [34,35]. In our study, the E values of the primers used to amplify the five candidate reference genes were between 94% and 98.5%.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Primer amplification efficiency indicates the amplicon doubling rate of a specific primer pair during a PCR, which affects the accuracy of RT-qPCR data [4,40]. A good primer combination has an E value close to 100% [34,35]. In our study, the E values of the primers used to amplify the five candidate reference genes were between 94% and 98.5%.…”
Section: Discussionmentioning
confidence: 70%
“…In these studies, it is vital to choose appropriate reference genes for obtaining accurate and reliable results. A good primer combination has an E value close to 100% [34,35]. However, there has been no systematic and accurate validation of these genes under various experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a normalization method is required for obtaining reliable and unbiased quantitative gene expression profiling of a target gene. (Reddy et al, 2015), and Apium graveolens L. (Li et al, 2016), have shown that the expression of the HKGs is not as stable as it was generally assumed. The reliability of the quantitative results of qRT-PCR depends on the selected reference gene(s).…”
Section: Identification Of Reference Genes For Qrt-pcr Gene Expressiomentioning
confidence: 94%
“…(Chandna et al, 2012), Arachis hypogea L. (Reddy et al, 2013), Vitis vinifera L. (Borges et al, 2014), Pennisetum glaucum (L.) R. Br. (Reddy et al, 2015), and Apium graveolens L. (Li et al, 2016), have shown that the expression of the HKGs is not as stable as it was generally assumed. It is risky to randomly choose any HKG to serve as a reference gene for qRT-PCR.…”
mentioning
confidence: 94%